Observation of the rare decay B+ → K+π0π0 and measurement of the quasi-two-body contributions B+ → K [ast] (892)+π0, B+ → [function]0(980)K+ and B+ → [chi]c0K+hJ.P. Lees, V. Poireau, V. Tisserand, J. Garra Tico, E. Grauges, M. Martinelli, D.A. Milanes, A. Palano, M. Pappagallo, G. Eigen, B. Stugu, L. Sun, D.N. Brown, L.T. Kerth, Yu. G. Kolomensky, G. Lynch, H. Koch, T. Schroeder, D.J. Asgeirsson, C. Hearty, T.S. Mattison, J.A. McKenna, R.Y. So, A. Khan, V. E. Blinov, A.R. Buzykaev, V.P. Druzhinin, V.B. Golubev, E.A. Kravchenko, A.P. Onuchin, S.I. Serednyakov, Yu. I. Skovpen, E.P. Solodov, K. Yu. Todyshev, A.N. Yushkov, M. Bondioli, D. Kirkby, A.J. Lankford, M. Mandelkern, D.P. Stoker, H. Atmacan, J.W. Gary, F. Liu, O. Long, G.M. Vitug, C. Campagnari, T.M. Hong, D. Kovalskyi, J.D. Richman, C.A. West, A.M. Eisner, J. Kroseberg, W.S. Lockman, A.J. Martinez, T. Schalk, B.A. Schumm, A. Seiden, C.H. Cheng, D.A. Doll, B. Echenard, K.T. Flood, D.G. Hitlin, P. Ongmongkolkul, F.C. Porter, A.Y. Rakitin, R. Andreassen, M.S. Dubrovin, B.T. Meadows, M.D. Sokoloff, P.C. Bloom, W.T. Ford, A. Gaz, M. Nagel, U. Nauenberg, J.G. Smith, S.R. Wagner, R. Ayad, W.H. Toki, B. Spaan, M.J. Kobel, K.R. Schubert, R. Schwierz, D. Bernard, M. Verderi, P.J. Clark, S. Playfer, J.E. Watson, D. Bettoni, C. Bozzi, R. Calabrese, G. Cibinetto, E. Fioravanti, I. Garzia, E. Luppi, M. Munerato, M. Negrini, L. Piemontese, R. Baldini-Ferroli, A. Calcaterra, R. de Sangro, G. Finocchiaro, M. Nicolaci, S. Pacetti, P. Patteri, I.M. Peruzzi, M. Piccolo, M. Rama, A. Zallo, R. Contri, E. Guido, M. Lo Vetere, M.R. Monge, S. Passaggio, C. Patrignani, E. Robutti, B. Bhuyan, V. Prasad, C.L. Lee, M. Morii, A.J. Edwards, A. Adametz, J. Marks, U. Uwer, [und weitere] (BABAR Collaboration) - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We report an analysis of charmless hadronic decays of charged B mesons to the final state K+π0π0, using a data sample of (470.9±2.8)×106 B¯¯¯B events collected with the BABAR detector at the Υ(4S) resonance. We observe an excess of signal events, with a significance above 10 standard deviations including systematic uncertainties, and measure the branching fraction and CP asymmetry to be B(B+→K+π0π0)=(16.2±1.2±1.5)×10−6 and ACP(B+→K+π0π0)=−0.06±0.06±0.04, where the uncertainties are statistical and systematic, respectively. Additionally, we study the contributions of the B+→K∗(892)+π0, B+→f0(980)K+, and B+→χc0K+ quasi-two-body decays. We report the world’s best measurements of the branching fraction and CP asymmetry of the B+→K+π0π0 and B+→K∗(892)+π0 channels.